Geometric and electrochemical properties of complexes consisting of two aminonaphthoquinone-bound Schiff-base ligands and MnII, FeII, NiII, CuII, or ZnII. (28th January 2015) - Hasegawa, Yuta; Nakamura, Haruki; Hattori, Yohei; Hoshiko, Ken; Kusamoto, Tetsuro; Murata, Masaki; Kume, Shoko; Nishihara, Hiroshi
Abstract : Graphical abstract: Novel metal complexes with aminonaphthoquinone-bound Schiff-base ligands were prepared. The isostructural complexes formed NNN-type octahedral coordination geometry in crystals. Structural and electrochemical studies revealed that the central metal ion played important roles in both the molecular and the electronic structures of the complexes, controlling their electron-responsive properties (redox functionalities). Abstract: Novel compounds of metals (M = Mn II, Fe II, Ni II, Cu II, Zn II ) with aminonaphthoquinone-bound Schiff-base ligands (PyNq) were prepared with the form M(PyNq)2 . The resulting isostructural complexes formed NNN-type octahedral coordination geometry in crystals. The degree of distortion from the ideal octahedral structure depended on the ionic radius of the metal ion, with larger ions leading to greater distortion. Electrochemical studies showed that Fe II (PyNq)2 exhibited the greatest inter-ligand interaction of the tested compounds, resulting in a possible mixed-valence state in [Fe II (PyNq)2 ] − . DFT calculations suggested that the efficient participation of Fe II 3d orbitals in the LUMO would facilitate the inter-ligand interaction. The central metal ion was shown to be important to both the molecular and the electronic structures of the M(PyNq)2 complexes, controlling their electron-responsive properties (redox functionalities).